PENGARUH METODE EKSTRAKSI TERHADAP AKTIVITAS ANTIOKSIDAN DAUN KEDONDONG (Spondias dulcis) MENGGUNAKAN METODE DPPH & FIC - Risda Waris; Asni Amin; Nur Aisa; Ahmad Adi Muhtarom; Muhammad Nasman Arief (Jurnal Fitofarmaka Indonesia, 2025)
Spondias dulcis plant is a tropical plant in the Anacardiaceae family. One of the plants from nature that has antioxidant properties. The aim of the research was to see the effect of variations in Spondias dulcis leaf extraction methods on the antioxidant activity of eliminating DPPH and FIC radicals. The % yield of various extracts from the maceration extraction method was 2.625%, UAE was 23.36% and digestion was 23.08%. screening of the phytochemical compound components of the ethanolic extract of Spondias dulcis leaves, the three variations of maceration extraction method, Ultrasonic (UAE) and digestion using thin layer chromatography using the eluent n-hexane: ethyl acetate (8:2) detected flavonoid and tannin content, while only the maceration extraction method was detected containing steroids, then the third alkaloid screening extraction variation was not detected. The conclusion is that the heating process in the digestive extraction method affects the antioxidant activity of the DPPH radical removal method of Spondias dulcis leaf extract, even though the percentage yield of extract from the digestive method is high (IC50 66,620 µg/mL) but the antioxidant activity is at a lower level and is classified as strong compared to extraction without maceration heating (IC50 38,979 µg/mL and UAE (IC50 29.838 µg/mL) are in the very strong category extraction and antioxidant activity of the FIC method in the ethanolic extract of Spondias dulcis leaves, the maceration extraction method IC50 342.72 µg/mL has a weak antioxidant activity category while the UAE extraction method (IC50 54.059 µg/mL) and digestion (IC50 83.093) are classified as strong. So the antioxidant activity method and DPPH reduction more effective than the Fe chelating method.